Self-organization of mesoscopic silver wires by electrochemical deposition - Zhong, Sheng; Koch, Thomas; Walheim, Stefan; Rösner, Harald; Nold, Eberhard; Kobler, Aaron; Scherer, Torsten; Wang, Di; Kübel, Christian; Wang, Mu; Hahn, Horst; Schimmel, Thomas (Beilstein Journal of Nanotechnology, 2014)
Long, straight mesoscale silver wires have been fabricated from AgNO3 electrolyte via electrodeposition without the help of templates, additives, and surfactants. Although the wire growth speed is very fast due to growth under non-equilibrium conditions, the wire morphology is regular and uniform in diameter. Structural studies reveal that the wires are single-crystalline, with the [112] direction as the growth direction. A possible growth mechanism is suggested. Auger depth profile measurements show that the wires are stable against oxidation under ambient conditions. This unique system provides a convenient way for the study of self-organization in electrochemical environments as well as for the fabrication of highly-ordered, single-crystalline metal nanowires.
Keywords: crystal growth; electrochemistry; electrodeposition; mesowires; nanoelectrochemistry; nanowires; self-organization; silver nanowires; silver nitrate; stability